Luna loves dance - Coelho, Joseph; Lumbers, Fiona (2021)
Today Luna has her dance tryout. Dance shoes-- check. Dance tutu-- check. Dance bag-- check. Most of the class can do the steps, but when it's Luna's turn she ... falls. How will she ever become a real dancer?
"First published in Great Britain in 2021 by Andersen Press Ltd." -- Title page verso.
Keywords: Dance -- Juvenile fiction; Determination (Personality trait) -- Juvenile fiction; Dance -- Fiction; Determination -- Fiction; Dance